Bovine Colostrum Modulates Myeloablative Chemotherapy–Induced Gut Toxicity in Piglets. Issue 7 (27th May 2015) - Pontoppidan, Peter EL; Shen, René L; Cilieborg, Malene S; Jiang, Pingping; Kissow, Hannelouise; Petersen, Bodil L; Thymann, Thomas; Heilmann, Carsten; Müller, Klaus; Sangild, Per T
Abstract: Background: Intensive chemotherapy frequently results in gut toxicity, indicated by oral and intestinal mucositis, resulting in poor treatment outcomes and increased mortality. There are no effective preventive strategies against gut toxicity and the role of diet is unknown. Objective: We hypothesized that the severity of chemotherapy-induced gut toxicity in early life is diet-dependent, and that intake of bovine colostrum (BC) provides better gut protection than an artificial milk replacer (MR). Methods: A total of 37 3-d-old pigs received for 6 d either intravenous saline control or myeloablative treatment with busulfan and cyclophosphamide, and were fed either BC or MR, resulting in the following 4 treatments ( n = 8–10/group): bovine colostrum plus saline control (Ctr-BC), milk replacer plus saline control (Ctr-MR), bovine colostrum plus busulfan and cyclophosphamide chemotherapy (BUCY-BC), and milk replacer plus busulfan and cyclophosphamide chemotherapy (BUCY-MR). The gut was collected for analysis 11 d after the start of chemotherapy. Results: Relative to the control groups, both busulfan and cyclophosphamide chemotherapy (BUCY) groups showed signs of gut toxicity, with oral ulcers, reduced intestinal dimensions, and hematologic toxicity. Diet type did not affect mucosal structure on day 11, but BUCY-BC pigs had less vomiting than BUCY-MR pigs (1 of 10 vs. 10 of 10, P < 0.05). Markers of intestinal function were higher (up to 20-fold greater galactose absorption and 2–3-fold greater brush border enzyme activity, all P < 0.05), and tissue inflammatory cytokine concentrations and serum liver enzyme values were lower in BUCY-BC than in BUCY-MR pigs (30–50% reductions in interleukin 6 and 8, aminotransferase, and bilirubin concentrations, P < 0.05). Gut colonization was not significantly affected except that BUCY pigs had lower microbial diversity with a higher abundance of Lactobacilli. Conclusion: BC may reduce gut toxicity during myeloablative chemotherapy in piglets by preserving intestinal function and reducing inflammation. Whether similar effects occur in children remains to be tested.